Impact of Dairy Cooperatives on Quality of Life Parameters: Gender Analysis (Indian Journal of Extension Education, 2010)
The dairy cooperatives collect milk on a daily basis from villages and convert it into various value added products, which are sold through various outlets thereby benefiting both the suppliers and the consumers. The objective of the present investigation was to study the impact of dairy cooperatives on the quality of life parameters of members of dairy cooperative society (DCS). The study was conducted in Haryana state, India on a sample of 200 members of dairy cooperative, comprising of 100 men and 100 women drawn from 10 villages of two districts viz. Hisar and Mahendergarh. The impact of dairy cooperative societies (DCS) on nine quality of life parameters viz. economic, nutrition and health, housing, material possession, domestic violence, personal grooming, educational, social, recreational was investigated on gender basis. The impact on quality of life showed that the ranks were highly significant on gender basis for economic, nutrition and health, material possession, personal grooming and education but were negatively related in case of domestic violence. The overall impact was significant with spearmen rank order correlation of 0.85.